TINJAUAN HUKUM ISLAM TERKAIT FENOMENA PERKAWINAN DI BAWAH TANGAN - Hidayat, Taufik; Arasid, Mohamad Ikrom; Hibar, Ujang (LPPM Universitas Bina Bangsa, 2024)
Matrimony represents an esteemed avenue for structuring family life, welcoming children, fostering mutual acquaintance, and establishing a foundation for reciprocal support. The institution of marriage establishes explicit shared rights and responsibilities between spouses, as well as between parents and offspring. In practice, not all adherents of Islam adhere to contemporary procedures or regulations, evident in the persistence of individuals opting for clandestine unions. Islamic jurisprudence has elevated the motives and objectives of matrimony to a loftier and more dignified plane. While previous adherence to Islamic doctrines limited the purpose of marriage to biological needs and life necessities, Islamic law now designates it with the intent of fulfilling sunnatullah, directed toward the ultimate goal of 'worshipping Allah SWT